Speech Acts Analysis of Prophecies and their Influence on the Clients. - Awogya , Awogya Rosemary; Abdulai, Abdulai Issah; Kufiah, Charles Wese (International Journal of Culture and Religious Studies, 2022)
Purpose: This paper examines the speech acts performed in prophecy by Prophets in Ghana. Methodology: Qualitative data was used comprising two prophesies and two directions of four prophets in the study. Appropriate data for the study has been elicited through audio recording of a T.V broadcasting of Prophecies by some selected prophets. The data obtained has been autographically transcribed and translated into English for easy analysis. Findings: The results show that speech acts such as assertives, commissives, directives, expressives and declaratives are all performed in prophecies. The study also reveals that the prophets are perceived to be "˜destiny changers' without them, their "˜clients' will not have salvation (Quayesi-Amakye, (2013). This explains why these people rely so much on prophets and become inactive and helpless to themselves. Unique Contribution to Theory, Policy and Practice: The study is creating the awareness of the general public to how end-time prophets employ language to exploit their church members, for that matter the general public. Austin (1969) in his book, "˜How to do Things with Words' talks about locutionary act, illocutionary force and per illocutionary effect of words on individuals. The study therefore cautions the general public to face the problems of life head on and not the problems of life head on and not to fall prey to these religious charlatans (Quayesi-Amakye (2013).